Neurotoxin‑induced rodent models of Parkinson’s disease: benefits and drawbacks - El-Gamal, Mohamed; Salama, Mohamed; Collins-Praino, Lyndsey E.; Baetu, Irina; Fathalla, Ahmed M.; Soliman, Amira M.; Mohamed, Wael Mohamed Yousef; Moustafa, Ahmed A. (Springer Nature, 2021)
Parkinson’s disease (PD), the second most common neurodegenerative disorder, is characterized by cardinal motor impair-ments, including akinesia and tremor, as well as by a host of non-motor symptoms, including both autonomic and cognitive dysfunction. PD is associated with a death of nigral dopaminergic neurons, as well as the pathological spread of Lewy bodies, consisting predominantly of the misfolded protein alpha-synuclein. To date, only symptomatic treatments, such as levodopa, are available, and trials aiming to cure the disease, or at least halt its progression, have not been successful. Wong et al. (2019) suggested that the lack of effective therapy against neurodegeneration in PD might be attributed to the fact that the molecular mechanisms standing behind the dopaminergic neuronal vulnerability are still a major scientific challenge. Understanding these molecular mechanisms is critical for developing effective therapy. Thirty-five years ago, Calne and William Langston (1983) raised the question of whether biological or environmental factors precipitate the development of PD. In spite of great advances in technology and medicine, this question still lacks a clear answer. Only 5–15% of PD cases are attributed to a genetic mutation, with the majority of cases classified as idiopathic, which could be linked to exposure to environmental contaminants. Rodent models play a crucial role in understanding the risk factors and pathogenesis of PD. Additionally, well-validated rodent models are critical for driving the preclinical development of clinically translatable treat-ment options. In this review, we discuss the mechanisms, similarities and differences, as well as advantages and limitations of different neurotoxin-induced rat models of PD. In the second part of this review, we will discuss the potential future of neurotoxin-induced models of PD. Finally, we will briefly demonstrate the crucial role of gene-environment interactions in PD and discuss fusion or dual PD models. We argue that these models have the potential to significantly further our under-standing of PD.